Suppression of falling leaf mode phenomenon for F/A - 18 via L1 adaptive feedback controller - Vijayakumar Meera (2017)
F / A - 18 Hornet aircraft is prone to nonlinear phenomenon known as the fulling leaf mode, which when operating at deep stall is often combined with large side slip and yaw motion resuhs in significant rotation. The resuhant rotation triggers the aircraft to lose ahitude at a very fuster rate. The intention of this work is to design LI adaptive controller for F / A - 18 aircraft intended to suppress the fulling leaf phenomenon. The design developed will be using Lyapunov's based adaptive laws to compensate for the uncertainties in design variable and comparing the associated performance with the conventional controller. The L 1 adaptive controller implementation to F / A -18 aircraft has proved good resuhs in eliminating the uncertainties when implemented and also proper selection of fiher in adaptive control design can handle uncertainties and disturbance well to track reference signal. Compared to the MRAC formulation introduction of fiher in LI is more robust to uncertain parameters. The performance study on implementing LI adaptive controller to the VA V is also found in this report. Resuhs indicate that introduction of fiher in LI adaptive controller provides good improvement in surpassing uncertainties with minimized effect on cost criteria. The resuhs of simulations show how efficient the controller is designed to separate adaption from robustness and the efficient way of handling performance bounds.